Effect of dose adjustment on enalapril-induced cough and the response to inhaled capsaicin. - Yeo, W W (1995)
1. In nine hypertensive patients with enalapril-induced cough the effect of altering the dose of enalapril on subjective cough and the cough response to inhaled capsaicin was examined in a random single-blind balanced cross-over study. They received three doses of enalapril, each for 3 weeks; the dose at entry (mean 10 mg daily); double this dose (mean 20 mg daily); and half this dose (mean 5 mg daily). 2. The cough response to inhaled capsaicin was also measured in two control groups: hypertensive patients on long-term enalapril treatment with no cough (n = 18), and hypertensive patients taking nifedipine (n = 17). 3. In patients with enalapril-induced cough there were significant dose-responses for enalapril as regards severity of cough (P < 0.05) and night time waking by cough (P < 0.05), but not for frequency of cough. Although the cough was less severe (P < 0.02) and caused less night time waking (P < 0.03) on the lowest dose of enalapril (mean 5 mg daily) it did not disappear completely in any patient. 4. The sensitivity to inhaled capsaicin did not differ significantly on the three doses of enalapril. The relative potency of capsaicin on enalapril 20 mg compared with enalapril 5 mg was 1.0 (95% CI 0.4-2.2). The wide confidence limits indicate that an important dose-dependent shift in capsaicin sensitivity is not excluded. 5. The sensitivity to inhaled capsaicin differed significantly between patients with enalapril-induced cough and both control groups.(ABSTRACT TRUNCATED AT 250 WORDS)